1997
DOI: 10.1086/604265
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Exit and Reentry among Family Shelter Users in New York City

Abstract: This study explores the process of exit from and reentry to public family shelters for homeless families in New York City. A Cox proportional-hazards model was developed to identify the effects of demographic, family structure, reason for homelessness, an time-related variables on the hazard rates for different types of shelter discharge and shelter reentry. The study specifically explores the significance of type of housing placement as a predictor variable for shelter reentry. Various demographic and family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
57
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 3 publications
7
57
1
Order By: Relevance
“…The number of children can provide a barrier to exiting shelter because it can be challenging to find affordable housing with the bedrooms needed for large families. This finding is consistent with earlier research (Wong et al 1997). The results suggest that the number of adults in a household can act as a protective factor.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The number of children can provide a barrier to exiting shelter because it can be challenging to find affordable housing with the bedrooms needed for large families. This finding is consistent with earlier research (Wong et al 1997). The results suggest that the number of adults in a household can act as a protective factor.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, using shelters in this way likely extends unnecessarily the length of stays for families that may have relatively few barriers to exit (Culhane et al 2007). However, given the strong relationship between housing stability and having a subsidy (Wong et al 1997;Shinn et al 1998;Rog and Buckner 2007), the financial cost of an extended shelter stay may be offset by savings realized through reductions in the rates of future homeless episodes (Wong et al 1997). Despite this, study results suggest the need for strategies that provide early housing support to families.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is an important contribution as research conducted to date using longitudinal administrative homelessness data has been limited to individuals accessing emergency shelter; these studies have consistently found that only a small minority of persons in shelter on a given night stay in shelter for an extended period of time. [25][26][27][28] The low rate of positive rescreens …”
Section: Discussionmentioning
confidence: 99%